Karst’s caves characteristics in Daryanah area, Al Jabal Al Akhdar, NE Libya - Ajazzwe, Abdearahime; Ashahomi, Khalifa (Libyan Journal of Science &Technology, 2022)
The genesis and development of karst caves in the Daryanah area have been detected through the study of cave chambers, passages and different types of cave deposits. It has been proved that caves were initiated and developed in the phreatic and vadose zone respectively. The studied caves are classified as small carbonate caves, formed along bedding planes of endogenic origin and developed according to simple model of limited recharging points.